OPTIMASI DETEKSI GEN PADA Stelechocarpus burahol (Bl.) Hook.f. & Th. MENGGUNAKAN DIRECT KIR PCR - Tri Suwarni Wahyudiningsih; Dian Sartika (Jurnal Pemuliaan Tanaman Hutan, 2020)
Purification of DNA molecules from a large number of samples is laborious, costly, time-consuming, and a high risk of contamination. S. burahol leaves contain phenolic compounds, flavonoids, and terpenoids that can interfere with DNA isolation. Direct PCR kits can detect genes without DNA extraction. The objective of study was to determine the method of gene detection of Stelechocarpus burahol using the direct PCR kit. S. burahol leaf samples came from the Bogor Botanical Gardens (two trees), Garut, Purwodadi Botanical Gardens, Kyai Langgeng Gardens, Yogyakarta Palace, Turi Sleman, Wanagama, Karanganyar, and South Kalimantan. Each leaf sample of 0.1 mg was dissolved into 1.25% w / v SDS (Sodium Dodecyl sulfate) 50 ul solution, incubated at 95o C for 5 minutes, and vortexed for 2 seconds. Primers used for the trials were ITS 1F primers and 4R primers. Pre-denaturation of 95oC for 7 minutes, denaturation of 95oC for 1 minute, annealing 55oC for 1 minute, extension at 72oC for 1 minute, extension at 72oC for 1 minute, and 40 cyclus. PCR product samples of 40 - 50 μl that showed positive results were detected by electrophoresis. The results of S. burahol DNA amplification measuring ± 750 bp from ten samples of S. burahol. Direct PCR kits can be used for S. burahol gene detection, time and energy efficient, only requires a small amount of tissue, and reduces contamination due to DNA extraction. Direct PCR kits can be an effective method that can be utilized to detect target genes for large populations